Incidence of the financial statements in the decision-making in the construction companies in the city of Huanuco 2017 - Huaynate-Delgado, Elías T. (2019)
The objective of this study was to determine the incidence of financial statements in the decision-making process in construction companies in the city of Huánuco 2017. The study method was basic, the type according to the nature of the study that was proposed. , meets the sufficient methodological conditions to be considered an "applied research", because it allows to analyze and interpret the financial statements as a valuable tool for decision making, before the development opportunity to which companies are dedicated to the construction of works of the district of Huánuco, The research was carried out according to its purposes, focusing on the "descriptive" level, since it allows obtaining all the relevant and necessary information to analyze and interpret the financial statements as support for the decision making of companies builders of public works of the district of Huánuco. The result shows that the 1260 data obtained 73.17% (922) affirm that they agree that there is a significant incidence between the financial statements and the decision making in the construction companies in the City of Huánuco 2017. While the 26.83% (338) of the respondents manifest their disagreement do not know do not think about it. It is concluded that, the financial statements, affects the decision making in the construction companies in the City of Huánuco 2017, as it has been demonstrated at the moment of carrying out the test of the General Hypothesis by means of the chi square test.